Reproduction of Discourse on the Issue of Data Leakage in Kominfo - Viola Geraldine; Daniel Susilo; Hilarius Bambang Winarko (Green Publisher Indonesia, 2025)
Data leaks are not only the responsibility of the government but also a shared responsibility individually. In July 2024, Kominfo experienced a ransomware attack that had an impact on the leak of people's personal data. Various responses from netizens on social media X pressured the government to immediately handle this case firmly. This study aims to look at the interactions formed in social media users X through a review of digital discourse on Kominfo's response in overcoming data leaks through the SCCT Coombs model. This study uses the digital discourse analysis method by analyzing the response of netizens in X in responding to the handling of the Kominfo crisis in the period of July 2024 – May 2025. The results of this study found a tendency of negative public sentiment towards the handling of the Kominfo crisis. Public response is influenced by perceived experience, cognition, and expectations to the government for handling data leaks. This research provides development insights for communication crisis practitioners and organizations, especially Kominfo, to optimize their communication crisis strategies based on digital media.